Reliability Analysis of Composite Laminated Plate with a Hole Subject to In-Plane Load - MUROTSU, Yoshisada; KOGISO, Nozomu; NAKAMURA, Masafumi (Transactions of the Japan Society of Mechanical Engineers Series A, 1999)
This study is concerned with the reliability analysis of the composite plate with a hole. The reliability is evaluated by modeling the plate as a series system consisting of each ply failure based on a first ply failure criterion. The mode reliability is obtained by the first order reliability method. where material strengths and applied loads are treated as random variables. The reliability is evaluated at the most critical point of each ply. The strength distribution is evaluated by the finite element analysis by adopting Tsai-Wu criterion. The system reliability is approximated by Ditlevsen's bounds. Through numerical calculations, the effect of variations of the random variables is discussed. Then, the reliability-based design is compared with the deterministic strength maximization design. Finally, it is shown that reliability is an important measure for structural safety.